PEMBERDAYAAN LEMBAGA MEDIASI DALAM PENYELESAIAN SENGKETA DI BIDANG PERTANAHAN - Sukresno Sukresno (Masalah-Masalah Hukum, 2012)
Operation of mediating institutions in order to perform its functions is part of the workings of the legal system that is affected by the component structure, substance and culture. The weakness of these components will affect the operation of mediating institutions are less effective and efficient so that was not optimal in resolving disputes in the area of land. Empowerment of the structure, substance and culture of mediating institutions are absolutely necessary in order to function effectively and efficiently. Problems discussed in this study, first, why the need for the empowerment of mediation in resolving disputes in the area of land, Secondly, why the use of mediation as an effort to institute a dispute settlement in the area of land is not maximized?; And third, how konkritisasi empowerment of mediation to be effective in dispute resolution in land? Above problems are analyzed with a frame of mind the theory of the workings of the legal system, theories of conflict resolution / dispute, the legal effectiveness of the theory and supported the idea and the concept of empowerment. With the legal paradigm constructivisme and socio legal research approaches, the primary and secondary data were processed using contextual understanding of the interpretation, evaluation of reliability and validity of the logical interaction (level of confidence) or credibility. The purpose of this study is to investigate, identify and evaluate the need for empowerment of mediation in dispute resolution in land and look for the cause not the maximum use of the mediation agency; and find a concretization of the effective empowerment of mediation in resolving disputes in the area of land. Establishment of mediation as an alternative dispute resolution in land is the newly born and grow and therefore has not developed into an effective institution. Empowerment of these institutions is absolutely necessary as there are still weaknesses of structural components, the substance and culture. The use of mediation by the institution of the National Land Agency / Office of Land there are problematic aspects that hinder making it less effective in maximizing the settlement of disputes in the area of ??land. Konkritisasi mediation for the empowerment of the structural components include planning, organizing and coaching facilities, infrastructure and human resources. Empowerment of the substance to amend legislation in the area of ??land including the set up and establish justice in land disputes. Empowerment of the culture is to instill traditional values ??in the form of institutional deliberation by entering the APS to formal and informal curriculum, utilizing the mass media, and other outreach programs. Keywords : Empower, Mediation Institution, Dispute of Land Affairs Sector.